2017
DOI: 10.1016/s1470-2045(17)30355-8
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan–temozolomide with temsirolimus or dinutuximab in children with refractory or relapsed neuroblastoma (COG ANBL1221): an open-label, randomised, phase 2 trial

Abstract: Background Outcomes for children with relapsed and refractory neuroblastoma are dismal. The combination of irinotecan and temozolomide (I/T) has activity in these patients, and the toxicity profile of I/T makes it an excellent backbone for study of new agents. Temsirolimus (TEM) and dinutuximab (DIN) were selected for testing with I/T in subjects with relapsed or refractory neuroblastoma. Methods Children’s Oncology Group (COG) ANBL1221, a randomised Phase II selection design trial, compared response and tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
235
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(241 citation statements)
references
References 55 publications
1
235
1
4
Order By: Relevance
“…’ Most patients in our series were managed with ICE at relapse, although some were treated with IT. The use of IT in combination with dinutuximab, an anti‐GD2 monoclonal antibody, is now a favored regimen given the recent (March 2015) FDA approval for primary therapy . Only one patient in our series was managed with anti‐GD2 monoclonal antibody at relapse and is alive at present with stable disease.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…’ Most patients in our series were managed with ICE at relapse, although some were treated with IT. The use of IT in combination with dinutuximab, an anti‐GD2 monoclonal antibody, is now a favored regimen given the recent (March 2015) FDA approval for primary therapy . Only one patient in our series was managed with anti‐GD2 monoclonal antibody at relapse and is alive at present with stable disease.…”
Section: Discussionmentioning
confidence: 87%
“…More recently, 5‐day IT has been shown to have favorable response rates, minimal organ toxicity, and limited immunosuppression, and as a result has become the backbone for addition of other agents . ’ Most patients in our series were managed with ICE at relapse, although some were treated with IT. The use of IT in combination with dinutuximab, an anti‐GD2 monoclonal antibody, is now a favored regimen given the recent (March 2015) FDA approval for primary therapy .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the data also revealed idasanutlin mediated downregulation of MTORC1 signalling which has previously been linked to chemoresistance and could therefore sensitise cells to temozolomide. However, a recent Phase II trial of irinotecan‐temozolomide with temsirolimus in children with refractory/relapsed neuroblastoma did not observe outcomes meriting further study . A recent study has reported potent preclinical efficacy combining the MTORC1 inhibitor temsirolimus with idasanutlin in neuroblastoma preclinical models .…”
Section: Discussionmentioning
confidence: 99%
“…[82] Preliminary results from a randomized phase II study conducted by the COG (NCT01767194) indicate a significantly higher response rate to a combination of dinutuximab, irinotecan, temozolomide and GMCSF compared to the combination of dinutuximab and temsirolimus (52.9% versus 5.5%), though the former group also had a higher complication rate including respiratory and renal toxicities. [83] A more definitive study of the chemoimmunotherapy arm is under way to further evaluate response and toxicity. A further chemoimmunotherapy strategy using hu3F8, though with different timing of therapeutic components is also being tested at MSKCC.…”
Section: Anti-gd2 Monoclonal Antibodiesmentioning
confidence: 99%
“…[83] Although these findings need to be confirmed in a larger population of patients, and the mechanism of synergy elucidated, the possible role of chemoimmunotherapy as part of first-line chemotherapy for HR-NB is being considered for investigation. MoAb-based radioimmunotherapy has thus far been hampered by collateral BM damage due to off-target effects.…”
Section: Five Year Viewmentioning
confidence: 99%